2020
DOI: 10.1055/s-0040-1701255
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Quality Face-to-Face Communication during Ophthalmology Encounters in the Electronic Health Record Era

Abstract: Objective To evaluate informatics-enabled quality improvement (QI) strategies for promoting time spent on face-to-face communication between ophthalmologists and patients. Methods This prospective study involved deploying QI strategies during implementation of an enterprise-wide vendor electronic health record (EHR) in an outpatient academic ophthalmology department. Strategies included developing single sign-on capabilities, activating mobile- and tablet-based applications, EHR personalization train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Looking at specific measures of EHR use reported in each study reveals additional differences, particularly regarding durations of EHR use ( Figure 4 ). Reported time-based measures included total time in the EHR (49 articles), 3 , 4 , 19 , 24–33 , 35–49 , 51–59 , 61 , 66 , 69–73 , 77 , 79 , 95 , 98 time in notes (32 articles), 3 , 4 , 7 , 19 , 24–32 , 35–38 , 40–46 , 48 , 51 , 55–58 , 79 , 109 time in inbox (23 articles), 2–4 , 19 , 24 , 25 , 27–29 , 35–38 , 42 , 43 , 45 , 47 , 48 , 51 , 61 , 62 , 70 , 71 time in chart review (23 articles), 3 , 4 , 24–27 , 29 , 31 , 32 , 35 , 36 , 40 , 42 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Looking at specific measures of EHR use reported in each study reveals additional differences, particularly regarding durations of EHR use ( Figure 4 ). Reported time-based measures included total time in the EHR (49 articles), 3 , 4 , 19 , 24–33 , 35–49 , 51–59 , 61 , 66 , 69–73 , 77 , 79 , 95 , 98 time in notes (32 articles), 3 , 4 , 7 , 19 , 24–32 , 35–38 , 40–46 , 48 , 51 , 55–58 , 79 , 109 time in inbox (23 articles), 2–4 , 19 , 24 , 25 , 27–29 , 35–38 , 42 , 43 , 45 , 47 , 48 , 51 , 61 , 62 , 70 , 71 time in chart review (23 articles), 3 , 4 , 24–27 , 29 , 31 , 32 , 35 , 36 , 40 , 42 , …”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies reported a measure based on a set time period, of which 7 unique periods were used (5:30 pm –8:30 am and 12:30 pm –1:30 pm , 5:30 pm –7 am , 6 pm –6 am , 6 pm –7 am , 7 pm –7 am , 7 pm –8 am , and 7:30 pm –7:30 am ). 4 , 6 , 19 , 25 , 27 , 29 , 32 , 34 , 36 , 39 , 40 , 42 , 48 , 49 , 51 , 53 , 55 , 66 , 69–71 An overlapping set of 22 articles, including 9 that also reported time period-based measures, reported at least 1 measure based on clinician schedules. 4 , 6 , 19 , 27 , 28 , 30 , 34 , 37 , 38 , 40 , 41 , 43 , 44 , 47–50 , 67 , 69 , 72 , 77 , 119 These included time outside scheduled hours on days with appointments, time on days without appointments, and time after the patient checked out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 However, EHR tools and predictive models can be used to optimize documentation and practice efficiency. 38 Prior studies have shown that although predictive modeling of EHRs has advanced rapidly, research describing actual implementation of these predictive models in clinical settings is lacking. 39 Finally, administrators may improve data collection by modifying the existing payment system (e.g., offering new incentives or developing new CMS evaluation and management coding guidelines) to reimburse providers for SDoH documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers assumed that it may take time to assimilate new practices and therefore we may see a change in perception early on but a return to baseline at 6 months as did other researchers. 19…”
Section: Samplementioning
confidence: 99%